Detailed procedures of retrofilling transformers with FR3 natural ester and residual mineral oil content testing. Issue 10 (22nd January 2022) - Wang, Yuan; Wang, Ruifeng; Pan, Kexin; Xu, Yang; Rapp, Kevin
Abstract: Several retrofillings have been performed by different utilities in China. However, there is still insufficient understanding of the retrofilling procedures for minimising residual mineral oil and on the effect of the temperature rise of transformers. Following new detailed procedures, an out‐of‐service S11‐M‐315/10 (10 kV 315 kVA) and a new S13‐M‐400/10 (10 kV 400 kVA) distribution transformers were selected to retrofill their mineral oil with FR3, a soybean‐based natural ester. A method was proposed to predict the residual mineral oil content, which uses the kinematic viscosity at 60°C. This method fills a gap in the testing of residual mineral oil content. The mass ratios of residual mineral oil were 1.24% for the S11‐M‐315/10 transformer and 2.05% for the S13‐M‐400/10 transformer, based on the procedures in this study. The fire point of the mixed oil after retrofilling was 352°C, which meets the K ‐class less‐flammable requirements, indicating a proper control of residual mineral oil. After retrofilling, the time of reaching the limits of the 1.5 times rated load was 30% longer than that of the mineral oil transformer. Two retrofilled transformers have been operating in good conditions since November 2019 for the S11‐M‐315/10 transformer and December 2020 for the S13‐M‐400/10 transformer.